Modeling the effects of channel noise in neurons - Guler, Marifi (World Scientific Publ Co Pte Ltd, 2006)
A framework for modeling the effects of channel noise in neurons is proposed through an adoption of stochastic mechanics within an approach based on the coupling between collective and intrinsic states. A model of the effects in a neuron of Rose-Hindmarsh type is introduced consequently. It is found, using the model, that even though the channel noise alters the neuron's quantitative behaviour, the repertoire of basic behaviour patterns remains to be the same; and that the region of bursting activity is extended to significantly higher input current values.
Keywords: channel noise; stochastic ion channels; bursting; modeling channel noise; Rose-Hindmarsh